How Adult Educators can Forge a Peaceful World - Hsiu-Chu Hsu (Adult Education Research Conference, 2008)
The purpose of this presentation is to explore some practical ways that adult educators can help to promote peace by including three less-discussed categories of adult education: popular education for critical citizenship, for nonviolence and constructive programs, and for holistic spirituality.
Keywords: peace; critical citizenship; nonviolence; spirituality; adult education